ESTUDIO DEL EMPAQUE PRIMARIO DURANTE EL PROCESO DE MADURACIÓN EN SALCHICHÓN CERVECERO CON ADICIÓN DE CULTIVO LÁCTICO (Lactobacillus delbrueckii Subsp. Bulgaricus y Streptococcus thermophilus) - Vera Cajamarca, Cristina María (2023)
Matured meat products are developed through a process that is crucial for achieving foods of optimum quality. In the Ecuadorian context, where the production of matured sausages is limited and much of it is imported, the possibility of improving local production through alternative approaches was explored. For this reason, the objective of this research was to study the primary packaging during the maturation process in Brewer's sausage with the addition of lactic culture (Lactobacillus delbrueckii Subsp. Bulgaricus and Streptococcus thermophilus). The maturation process was carried out in an artisanal manner in Cantón Valencia, using a trifactorial AxBxC design according to the factors: A (Type of primary packaging), B (Days of maturation) and C (Percentage of lactic culture), with three replicates. The results were analyzed using three statistical programs: Statistica for microbial growth kinetics according to the Gompertz model, Infostat and StatGraphics for statistical differences in bromatological parameters. The most outstanding treatments, in line with NTE INE 1338 regulations and previous studies, were the following: T6: Edible Collagen Casing, 12 days of maturation and 0.2 % of lactic culture; T7: Edible Collagen Casing, 14 days of maturation and 0.1 % of lactic culture; and T8: Edible Collagen Casing, 14 days of maturation and 0.2 % of lactic culture, when passing to the evaluation of acceptability through the affective test performed on 70 students, revealed that T7 was the best valued, consolidating as the best study treatment. In summary, these results have the potential to boost local production of matured sausages and reduce dependence on foreign imports, presenting an opportunity for innovation in the Ecuadorian food industry, as well as highlighting the importance of exploring alternative approaches to improve the quality and sustainability of food production.